Microsoft Windows security essentials. - Gibson, Darril, ....- (Indianapolis : Wiley, 2011)
IT security can be a complex topic, especially for those new to the field of IT. This full-color book, with a focus on the Microsoft Technology Associate (MTA) program, offers a clear and easy-to-understand approach to Windows security risks and attacks for newcomers to the world of IT. By paring down to just the essentials, beginners gain a solid foundation of security concepts upon which more advanced topics and technologies can be built. This straightforward guide begins each chapter by laying out a list of topics to be discussed, followed by a concise discussion of the core networking skills you need to have to gain a strong handle on the subject matter. Chapters conclude with review questions and suggested labs so you can measure your level of understanding of the chapter's content. > Serves as an ideal resource for gaining a solid understanding of fundamental security concepts and skills > Offers a straightforward and direct approach to security basics and covers anti-malware software products, firewalls, network topologies and devices, network ports, and more > Reviews all the topics you need to know for taking the MTA 98-367 exam > Provides an overview of security components, looks at securing access with permissions, addresses audit policies and network auditing, and examines protecting clients and servers
Keywords: Computernetwerken -- Beveiliging; Windows